Pengaruh Pembelajaran Kewirausahaan dan Motivasi Kewirausahaan terhadap Minat Menjadi Pengusaha Muda pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Mamuju - Saputra, Hadi Eka; Nanda, Giri Dwi; Fitriany, Fitriany; Tahir, Muh (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Indonesia is a country with a large population and abundant natural resources. The high unemployment rate remains a challenge that needs improvement and can become a recurring problem. Learning about entrepreneurship and self-support are essential factors that young generations can focus on. At the university level, entrepreneurship education is integrated into lectures to foster entrepreneurial skills. This study aims to analyze the influence of entrepreneurship education and entrepreneurial motivation on the interest in becoming a young entrepreneur among students of the Faculty of Economics and Business at Muhammadiyah University of Mamuju. This research uses a quantitative method with data collected through questionnaires distributed to 177 students. Data was analyzed using multiple linear regression tests to test the proposed hypotheses. The findings show that both entrepreneurship education and entrepreneurial motivation have a positive and significant influence on students’ interest in becoming young entrepreneurs. These results align with Yuritanto & Armansyah’s study, which stated that entrepreneurship education significantly affects the entrepreneurial interest of Management students. The conclusion of this study is that the interest in becoming a young entrepreneur is influenced by entrepreneurship education and entrepreneurial motivation that arises both internally and externally.